Kompensasi, kepuasan kerja dan komitmen karyawan pada Hotel De’boutique Malang - Dian Tri Mahardini; Kristina Sedyastuti; Endi Sarwoko; Andi Nu Graha (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2021)
This study aims to analyze the effect of compensation on employee commitment, and the effect of job satisfaction on employee commitment. Using a quantitative research approach using a questionnaire to measure the responses of all employees of Hotel De 'Butik Malang, totaling 63 people. The research instrument was arranged using a 5 interval Likert scale. Data analysis and hypothesis testing using Multiple Linear Regression and t-test. The results of the study explain that compensation will affect employee commitment to the organization, besides that job satisfaction is also a factor that affects employee commitment at Hotel De'Boutique Malang. Future research can develop a research model by examining the mediating role of job satisfaction on the effect of compensation on employee commitment.